New Travelling Wave Solutions for KdV6 Equation Using Sub Equation Method - Durur, Hülya; Kurt, Ali; Tasbozan, Orkun (Applied mathematics and nonlinear sciences, 2020)
This paper proposes obtaining the new wave solutions of time fractional sixth order nonlinear Equation (KdV6) using sub-equation method where the fractional derivatives are considered in conformable sense. Conformable derivative is an understandable and applicable type of fractional derivative that satisfies almost all the basic properties of Newtonian classical derivative such as Leibniz rule, chain rule and etc. Also conformable derivative has some superiority over other popular fractional derivatives such as Caputo and Riemann-Liouville. In this paper all the computations are carried out by computer software called Mathematica.